El crecimiento del sector construcción y su relación con la recaudación tributaria del departamento de Loreto periodo 2007 – 2022 - Angles Morales, Marco Sergio (2024)
This study examines the relationship between the growth of the construction sector and tax collection in the Department of Loreto, Peru, during the period 2007-2022. Using statistical methods to analyze data collected on production, growth rate of the construction sector, its proportion to GDP, income from internal taxes, total tax collection and number of taxpayers, the research seeks to understand how the dynamics of the construction sector impact efficiency . in regional tax collection. The results indicate a positive evaluation between the growth of the sector and tax collection, although moderate, suggesting that other factors such as economic policy and administrative effectiveness also influence these results. Furthermore, a strong relationship was found between the level of production of the sector and income from internal taxes, as well as between the ratio of production to GDP and the number of taxpayers, highlighting the importance of the sector in expanding the tax base and in promoting tax compliance. These findings highlight the need for policies that promote the growth of the construction sector along with improvements in tax collection and administration systems to maximize economic and fiscal benefits in Loreto.